Influence of pH on bioplastic production from Sweet Potato Starch (Ipomea batatas L.) - Salah, Roumaissa Ahmed; Alia, Zeid; Gahtar, Abdelouahab; Belahcene, Samira; Khechekhouche, El Amine; Amara, DjilaniGhemam (Future Science, 2025)
Scientists are exploring biodegradable bioplastic polymers as alternatives to traditional plastics to address environmental concerns. Bioplastics are derived from renewable materials such as starch, vegetable oils, and other organic sources. This study specifically focuses on using sweet potatoes to produce a bioplastic. Sweet potatoes are a versatile and nutritious crop that is widely grown around the world. The roots of sweet potatoes contain starch, which makes up a significant part of their composition. Starch is a valuable food source with industrial uses, including as a carrier medium for various substances in the food and pharmaceutical industries. The research was conducted in the Souf region of the Algerian Sahara, where sweet potato starch is obtained through a multi-step process that includes washing, peeling, filtering, and drying. This starch (5g) is mixed with 50 ml of water, hydrochloric acid, and glycerol (5 ml), then heated and dried to create bioplastics. The results show that the starch yield from sweet potatoes varies depending on the pH of the extraction medium, with the highest yield being achieved with a neutral medium (7.6±1.72 g). This study also investigates the potential of recycling industrial food waste, lovely potato peelings, for the production of bioplastics. It highlights the importance of pH in starch extraction and its subsequent use in bioplastics production, highlights environmentally friendly alternatives to traditional plastics, and contributes to the ongoing efforts to reduce plastic waste and pollution.